Fatwa Mengadakan Kubur Bertingkat, Perbahasan Dari Perspektif Malaysia - Md. Yunus Abd Aziz (Universiti Sains Islam Malaysia, 2024)
Limited and scarce land for burial purposes and the rapid increase of population have led to the proposal to reuse the graveyards. Several approaches were suggested to overcome these problems and among those being proposed was the development of multi-level graveyards. This proposal has been put forth to the authorities especially the muftis in relation to its Islamic legal ruling. The fatwa issued by the authority received mixed reaction from the public. This article intends to discuss the proposal to build multi-level graveyards by looking at the opinions of the earlier jurists and fatwas issued by muftis in Malaysia in matters concerning corpses and the use of cemetery. It is hoped that the analysis will assist in answering numerous questions arising out of the issue.